Theoretical Study of the Two-Dimensional Momentum Spectra of H- Ion in the Intense Laser Fields (Journal of Atomic and Molecular Sciences, 2014)
By using two model potentials chosen, the second outermost back rescatteredridges (BRR) of the two-dimensional (2D) momentum spectra of $H^-$ ion in thelinear polarization laser fields are studied under the strong-field approximation (SFA).The results show that the polarization potentials in the two model potentials havelittle effect on the 2D momentum spectra, the number of BRR increases and the fluctuationof angular distributions along the second BRR decreases with the increase of thelaser intensity, but the accurate electron-atom elastic scattering cross sections can beretrieved directly along the second outermost BRR by the polynomial fitting method.